Effects of auxins on the stem cuttings of Justicia Adhatoda L. - Uddin, Mohammed Sala; Rashid, Mohammad Harun Ur (Bangladesh Journal of Botany, 2023)
Justicia adhatoda L. (Bashak) is an evergreen, medicinal shrub belongs to the family Acanthaceae. The seeds germination quality of the species is very poor. The effects of auxins viz. IAA, IBA and NAA on the stem cuttings of the plant were assessed. A total of 13 treatments were applied on the stem cuttings and planted in sandy bed following completely randomized design. Results revealed that the maximum number of roots (28.67), length of roots (14.10 cm) and biomass (12.78g) were obtained at 90 days after planting in the cuttings treated with IBA 1000 ppm solution. Whereas, number of roots (21.67 and 22.67), length of roots (11.30 and 15.17 cm), biomass (8.56 and 12.17g) were obtained at 90 days after planting in the cuttings treated with IAA and NAA 1000 ppm solution respectively. IBA 1000 ppm solution would be considered as the most suitable for producing maximum number of roots and biomass, as well as NAA 1000 ppm solution for length of roots in Bashak at 90 DAP. Bangladesh J. Bot. 52(3): 861-865, 2023 (September)